The Population Size and Distribution of Diurnal Large Wild Mammals in the Southern Great Rift Valley, Ethiopia - Yacob Kassa; Wondimagegnehu Tekalign (The Scientific World Journal)
The study was carried out to assess the population size and distribution of diurnal large wild mammals in the southern Great Rift Valley, Ethiopia. The study area was stratified into four habitat types: riverine forest, ground-water forest, grassland, and bushland. Samples of animals were surveyed through the transect method. The total number of individuals belonging to the 15 species observed was 1681 and 1245 during the wet and dry seasons, respectively. Burchell’s zebra (Equus burchellii), Anubis baboon (Papio anubis), Vervet monkey (Chlorocebus pygerythrus), and Grant’s gazelle (Nanger granti) were the most abundant species, while Abyssinian hare (Lepus habessinicus) and Bush duiker (Sylvicapra grimmia) were the least abundant species. The highest number of species has been supported by the bushland habitat, followed by open grassland, riverine forest, and ground-water forest in both seasons. Despite the park being home to various types of mammalian species, there is a need for conservation actions by the park management and other concerned bodies for the survival of those species in the area.